2005
DOI: 10.1007/s10803-004-1035-5
|View full text |Cite
|
Sign up to set email alerts
|

Weak Central Coherence and Its Relations to Theory of Mind and Anxiety in Autism

Abstract: Recent theory and research suggests that weak central coherence, a specific perceptual-cognitive style, underlies the central disturbance in autism. This study sought to provide a test of the weak central coherence hypothesis. In addition, this study explored the relations between the weak central coherence hypothesis, theory of mind skills, and social-emotional functioning in a group of high functioning children with autism. Results revealed equivocal support for the weak central coherence hypothesis, but fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 46 publications
3
73
0
1
Order By: Relevance
“…A local processing bias and poor global processing have been observed in children with ASD, regardless of whether they pass or fail ToM tasks (Happé, 1994(Happé, , 1997. Burnette et al (2005) found a link between verbal measures of CC and ToM ability, but this was no longer significant once IQ was taken into account. A similar pattern of results was noted by Pellicano et al (2006) who found that correlations between performance in ToM and weak CC measures disappeared once age, verbal ability and non-verbal ability were accounted for.…”
Section: And Tommentioning
confidence: 95%
“…A local processing bias and poor global processing have been observed in children with ASD, regardless of whether they pass or fail ToM tasks (Happé, 1994(Happé, , 1997. Burnette et al (2005) found a link between verbal measures of CC and ToM ability, but this was no longer significant once IQ was taken into account. A similar pattern of results was noted by Pellicano et al (2006) who found that correlations between performance in ToM and weak CC measures disappeared once age, verbal ability and non-verbal ability were accounted for.…”
Section: And Tommentioning
confidence: 95%
“…Additionally, not all studies looking at performance on the block design task have found an autistic advantage (see White et al 2009 for a review). In fact, besides a number of studies reporting no difference between groups, one study found impaired rather than enhanced performance in autism on three visuospatial tasks (Burnette et al 2005).…”
mentioning
confidence: 96%
“…Some authors have calculated the average reaction time for correct responses only (de Jonge et al 2006;Morgan et al 2003;Pellicano et al 2005), whilst others have used the reaction time to all stimuli, either substituting the maximum time allowed for incorrect trials (Jarrold et al 2005;Jolliffe and Baron-Cohen 1997;Kaland et al 2007;Ropar and Mitchell 2001) or including search time regardless of whether the response was correct or not (Edgin and Pennington 2005). Burnette et al (2005) recently combined reaction time with accuracy by awarding an extra point for each trial in which correct reaction time was faster than a cut-off, and de Jonge et al (2006) required subjects to keep attempting each trial until they correctly identified the hidden shape up to a maximum time limit.…”
mentioning
confidence: 99%